In vitro evaluation of wound healing properties of fractions and extracts of Acrostichum Aureum Linné and A. Speciosum Willd - Herman, Hendy Putra; Darnis, Deny Susanti; Saad, Shahbudin; Bakhtiar, M. Taher; Ramli, Norazsida (Ibnu Sina Institute, UTM, 2012)
Medicinal use of Acrostichum aureum and A. speciosum in wound healing treatment by Malay community was tested scientifically in this project. Wound healing properties of ethanolic, aqueous extracts and the fractions of A. aureum and A. speciosum were evaluated in vitro using scratch wound assay on NIH/3T3 cell line. In total, 22 different extracts and fractions from leaves, stems, and rhizomes of both species were used for this testing. NIH/ 3T3 cell lines were seeded at a density of 5 x 104 cells/ mL in 24-well plate and incubated at 37°C until reaching nearly confluence. The confluent cell monolayer was manually scratched with a sterile pipette tip. This test was done in triplicate. For the treatment, each well was treated with 0.2 mg/ mL of the different extracts, 2 ng/ mL of platelet derived growth factor (PDGF) as positive control and DMEM medium as negative control. The images before treatment and after 12 hour post-treatment were photographed using ProgRes® CapturePro 2.5 software to measure mean migration rate (μm/hour) and open image area (%) using TScratch software. The results showed that cell line treated with aqueous extract of rhizomes and stems of both species have improved the migration rate. The fractions of A. aureum (n-Hexane, n- Hexane: DCM, and ethanol) and fractions of A. speciosum (n-Hexane, n- Hexane: DCM, and DCM) have shown enhancing effect in wound healing. These results strongly suggested the beneficial effects of both plant extracts for wound healing treatment and thus justified their medicinal use.